Peran Teori "Discovery Learning" Jerome Bruner Dalam Pembelajaran Pendidikan Agama Islam - Binti Khoiriyah Khoiriyah; Murniyati Murni (Thawalib: Jurnal Kependidikan Islam, 2021)
Learning is not merely a relationship between stimulus and response, but learning from the point of view of cognitivism is a deep thought process. Cognitivism prioritizes the learning process rather than learning outcomes and reveals that there is a need for learning methods that can activate student cognitive in the learning process. Jerome Bruner provides 3 stages of learning that can influence children's cognitive development, namely through active, iconic and symbolic learning. Bruner, who is an expert in cognitive developmental psychology, contributed discovery leaning learning theory or often called discovery learning. Bruner has also provided a cognitive learning step that he designed with six learning steps, starting from stimulation, problem identification, data collection, data processing to verification and conclusion drawing. The research was conducted qualitatively through observation and interviews by looking at the role of discovery learning theory in Islamic Islamic education learning at SMPN 3 Kalasan Sleman Yogyakarta. The results of the study reveal that discovery learning theory is very beneficial for students' cognitive development which is also well implemented, although not all learning materials can use this theory.